Rozwiązane

Rozwiąż równanie 5z+c=-3
-1z+c=5
Metoda przeciwnych współczynników



Odpowiedź :

[tex]\left \{ {{5z+c=-3|*(-1)} \atop {-1z+c=5}} \right. \\\left \{ {{-5z-c=3} \atop {-1z+c=5}} \right. \\+-----\\-6z=8\\z=-\frac{8}{6} =-\frac{4}{3}\\\\-1z+c=5\\-1*(-\frac{4}{3} )+c=5\\\frac{4}{3} +c=5\\c=5-\frac{4}{3} \\c=\frac{15}{3} -\frac{4}{3} =\frac{11}{3} \\c=\frac{11}{3}[/tex]

[tex]5z+c = -3\\-z + c = 5 \ \ |\cdot(-1)\\\\5z+c = -3\\z-c = -5\\------- \ \ + \ \ (dodajemy \ stronami)\\6z = -8 \ \ /:6\\z = -\frac{4}{3} = -1\frac{1}{3}\\\\c =5+z = 5-1\frac{1}{3} = 4\frac{3}{3}-1\frac{1}{3} = 3\frac{2}{3}\\\\\{c = 3\frac{2}{3}\\\{z = -1\frac{1}{3}[/tex]

Inne Pytanie